Effect of workplace bullying on self-esteem with moderating role of defense styles: a study among pharmacists in Sanaa, Yemen - Anam Mehmood; Umbreen Khizar; Sultan Mehmood Siddiqi; Rabia Mahmood; Mikiyas Amare Getu; Alariqi Reem (Taylor & Francis Group, 2024)
Background Workplace bullying is a widespread occurrence that has been identified as a significant concern in enterprises all around the world. The research aimed to examine the impact of workplace bullying on self-esteem among pharmacists with the moderating role of defense styles.Method This study utilised stratified random sampling to include 498 pharmacists from public and private hospitals in Sanaa, Yemen. Data was collected through structured questionnaires on demographics, workplace bullying (NAQ-R), self-esteem (Rosenberg scale), and defense styles (DSQ-40). Data analysis involved descriptive statistics, regression, correlation, T-tests, and moderation analysis.Results Results of the current study showed that workplace bullying has a significant negative impact on self-esteem, and defense styles do not moderate self-esteem and workplace bullying. Female pharmacists have higher workplace bullying and lower self-esteem. Gender differences in defense styles have insignificant results.Conclusion This research supports overcoming workplace bullying among employees in any organisation. Comprehensive anti-bullying policies must be developed and implemented to create a safe and supportive workplace for pharmacists. Anti-bullying strategies that promote gender equality address power disparities and guarantee that female employees have access to particular resources for support should incorporate gender-sensitive practices. In order to reduce the adverse effects of workplace bullying on mental health and boost the self-esteem of victims by offering counseling services, frequent training sessions, and seminars. It is also helpful in enhancing self-esteem and improving interpersonal relationships among employees.